Ouvidoria como instrumento de cidadania, controle social e avaliação de políticas de saúde no estado de São Paulo - Pereira, Regina Marta da Luz (2024)
Introduction: The Federal Constitution of 1988, in its article 37, § 3º, ensures the active participation of citizens in the social control of public management, highlighting the importance of participative democracy. In Brazilian public administration, ombudsman services are structured to promote society's participation in management, allowing citizens to express their demands and opinions on public services. Health ombudsman offices provide users with a channel to voice their concerns, actions, services, and health policies. Manifestation is a way for citizens to convey their desires, doubts, opinions, and satisfaction regarding a service or care received. Objective: To evaluate the manifestations of users of health facilities in the state of São Paulo (ESP), presented through the health services' ombudsman channels, available in the official database of the SUS-SP Ombudsman System, from 2018 to 2022. Methods: This is an observational, descriptive, exploratory study with a quantitative approach, conducted based on the manifestations registered with the General Ombudsman of the Unified Health System of the São Paulo State Health Department, which currently comprises a network of 293 public health system ombudsman offices. Results: Between 2018 and 2022, 533,380 manifestations were recorded, with the majority - 122,870 (23.04%) - in the year 2022. This study identified the main characteristics of the citizens' complaints to the General Ombudsman of SUS SES/SP, the majority of which (59.89%) were sent by users themselves, with personal identification, through letters or physical ballot boxes (38.92%). The main reasons for manifestations were related to management issues (68.23%) and health care (26.08%). In the general classification of demands, compliments were more present (41.70%), and most were considered low priority by the institution. Conclusion: The study allowed for a more comprehensive understanding of the demands and concerns presented by citizens regarding the health services used, housed by the various municipalities of São Paulo, as well as identifying critical points and potential areas for improvement within the health system.